Clonal Complex 398 Methicillin-Resistant Staphylococcus aureus Producing Panton-Valentine Leukocidin, Czech Republic, 2023 - Kristýna Brodíková; Thibault Destanque; Marisa Haenni; Renáta Karpíšková (Emerging Infectious Diseases)
To trace evolution of Panton-Valentine leucocidin–positive clonal complex 398 methicillin-resistant Staphylococcus aureus (MRSA) in the Czech Republic, we tested 103 MRSA isolates from humans. Five (4.9%) were Panton-Valentine leucocidin–positive clonal complex 398, sequence types 1232 and 9181. Spread to the Czech Republic may result from travel to or from other countries.